Intraocular Pressure Changes of Healthy Lowlanders at Different Altitude Levels: A Systematic Review and Meta-Analysis - Yang, Yiquan; Xie, Yuan; Sun, Yunxiao; Cao, Kai; Li, Shuning; Fan, Sujie; Huang, Lu; Wu, Shizheng; Wang, Ningli (Frontiers in Physiology, 2019)
Background: High altitude, characterized by hypobaric hypoxia, low temperature and intensive ultraviolet radiation, is identifiably one of the examples of scientific enquiry into aviation and space analogs. However, little is known about the ocular physiological response, especially intraocular pressure (IOP) changes at high altitude. Objectives: This study aimed to systematically review of high altitude exposure on IOP for healthy lowlanders with unoperated eyes. Methods: A comprehensive systematic literature search was conducted in the electronic databases until September 1st, 2019. A meta-analysis was performed following the preferred reporting items for systematic review and meta-analysis statement (PRISMA). We systematically searched the studies conducted over 2,000m above sea level (a.s.l) in healthy lowlanders with measurements of IOP. Meta-analyses (random effect model and heterogeneity tests), subgroup analyses (altitude, duration, type and pattern of exposure), sensitivity analysis, funnel plot, Begger’s and Egger’s test for publication bias were performed. Quality assessment was conducted using the Newcastle–Ottawa scale. The meta-analysis was registered in the PROSPERO database (CRD42019136865). Results: Of 9595 publications searched, 20 publications (n=745) qualified for inclusion, with non-significant decrease in overall IOP (standardized mean difference (SMD): 0.14, 95% CI: -0.12 - 0.40; p=0.30) with high heterogeneity (p<0.001, I2=82%). However, subgroup analyses revealed significant decrease of IOP at high altitude of 3,000-5,500m a.s.l (SMD: 0.57, 95% CI: 0.07 - 1.06; p=0.03) whereas increase of IOP at extreme altitude of over 5,500m a.s.l (SMD: -0.34, 95% CI: -0.61 - 0.06; p=0.02). And the duration of exposure more than 72 hours (h) was likely to induce a decrease of IOP bordering on statistical significance at the 5% level (SMD: 1.29, 95% CI: 0.02 - 2.56; p=0.05). Simultaneously, we also observed significant decrease of IOP for active exposure (e.g. physical activity and hiking, SMD: 0.81, 95% CI: 0.05 - 1.57; p=0.04). Conclusion: Our analysis shows exposure to the altitude over 3,500m a.s.l, duration of exposure more than 72h and active exposure pattern may have modest, but significant effects on IOP. The higher altitude, the duration of exposure as well as physical activity seem to play crucial roles in the effects of high-altitude exposure on IOP.